(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background:Intramuscular loading dose of Magnesium Sulphate could be a suitable alternative for community intervention of the management of severe Pre- Eclampsia and Eclampsia. Objective: To compare the efficacy of the loading total IM regime of injection Magnesium Sulphate (MgSO4) with the standard loading combined IV and IM regime for termination & prevention of recurrent convulsions in the treatment of Eclampsia. Methods: Total 200 patients were studied at Dhaka Medical College Hospital, Bangladesh from October 2012 to May 2013 where 100 patients were treated with loading IM regime (Case group) and 100 patients received standard loading combined IV & IM regime (Control Group). The efficacy of both regimes was measured by the rate of recurrent convulsions. Results: No significant differences was observed in both groups in terms of age (23.03±3.90 vs 23.34±4.63 years), parity (64% vs 63% primi), gestational age (36.39±3.64 vs 36.13±3.95 weeks),no of convulsions (5.28±3.21 vs 5.35±3.31 times), mean diastolic blood pressure (98.74±17.22 vs 104.25±15.43 mmHg) and Glasgow Coma Scale (e8, 96% vs<8, 92%). No significant differences observed between the two groups in mean convulsion to treatment interval (5.16±3.71 vs 4.95±3.12 hr) and convulsion to delivery interval (13.26±8.8 vs 13.95±8.46 hr). The recurrent convulsion rate was almost same in both groups (3% vs 5%, ð2 = 0.521, P> 0.05ns). Case fatality was 2% in case group and 3% in control group (P > 0.05ns). Conclusions: Loading total IM regime of MgSO4 is found as effective as the loading combined IV and IM regime in terms of control of convulsions and prevention of recurrent fits in Eclampsia. So it could be used by the field level workers before referral. J Bangladesh Coll Phys Surg 2016; 34(2): 85-91